Prognostic and predictive role of [18F]fluorodeoxyglucose positron emission tomography (FDG‐PET) in patients with unresectable malignant pleural mesothelioma (MPM) treated with up‐front pemetrexed‐based chemotherapy. (21st September 2017) - Zucali, Paolo Andrea; Lopci, Egesta; Ceresoli, Giovanni Luca; Giordano, Laura; Perrino, Matteo; Ciocia, Gianluigi; Gianoncelli, Letizia; Lorenzi, Elena; Simonelli, Matteo; De Vincenzo, Fabio; Setti, Lucia Rebecca; Bonifacio, Cristiana; et al.
Abstract: The aim of this study was to evaluate the role of metabolic parameters analyzed at baseline and at interim FDG‐PET in predicting disease outcome in unresectable MPM patients receiving pemetrexed‐based chemotherapy. A consecutive series of MPM patients treated between February 2004 and July 2013 with first‐line pemetrexed‐based chemotherapy, and evaluated by FDG‐PET and CT scan at baseline and after two cycles of chemotherapy, was reviewed. Best CT scan response was assessed according to modified RECIST criteria. Progression‐free survival (PFS) and overall survival (OS) were correlated with FDG‐PET parameters, such as maximum standardized uptake value (SUVmax ), total lesion glycolysis (TLG), and percentage changes in SUVmax (∆SUV) and TLG (∆TLG). Overall, 142 patients were enrolled; 77 (54%) received talc pleurodesis before chemotherapy. Baseline SUVmax and TLG showed a statistically significant correlation with PFS and OS ( P  < 0.05) in both group of patients (treated and untreated with pleurodesis). In 65 patients not receiving pleurodesis, SUVmax reduction ≥25% (∆SUV ≥ 25%) and TLG reduction ≥30% (∆TLG ≥ 30%) were significantly associated with longer PFS ( P  < 0.05). Patients showing both ∆SUV ≥ 25% and ∆TLG ≥ 30% responses had a significant reduction in the risk of disease progression (HR:0.31, P  < 0.001) and death (HR:0.52, P  = 0.044). Neither ∆SUV nor ∆TLG showed similar association with survival outcomes in patients treated with pleurodesis. Our study confirmed the prognostic role of baseline FDG‐PET in a large series of MPM patients treated with first‐line pemetrexed‐based chemotherapy. Moreover, use of ∆SUV ≥ 25% and ∆TLG ≥ 30% as cut‐off values to define early metabolic response supported the role of FDG‐PET in predicting disease outcome and treatment response in patients not receiving pleurodesis. Abstract : Our data confirmed the prognostic role of baseline FDG‐PET in a large series of MPM patients: baseline SUVmax and TLG statistically significantly correlate with PFS and OS in all population. In patients without pleurodesis, the FDG‐PET is able to predict treatment response: both ∆SUV ≥ 25% and ∆TLG ≥ 30% responses have a statistically significant lower risk of PD and death.